Bibliometric Analysis of Water Pollution Research: Focus on Industry Impacts - Mellyzar, Mellyzar; Hernani, Hernani; Nahadi, Nahadi; Agustina, Sri (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
Water pollution is a pressing global issue, particularly in regions heavily impacted by industrialization. This results in aquatic ecosystem degradation, biodiversity loss, and significant health risks from waterborne diseases and prolonged exposure to toxic pollutants. Industrial waste is a key contributor, highlighting the urgency of effective mitigation strategies. This study aimed to analyze research trends in industrial water pollution, identify knowledge gaps, and provide actionable insights for policymakers. A bibliometric analysis and literature review were conducted on 2,523 articles published between 2015 and 2024 using R software and the Biblioshiny interface. In addition, 30 highly cited articles were reviewed in-depth to explore dominant themes and advancements. The findings show a marked increase in research output, with China as the leading contributor. Key topics include the impact of industrial effluents, innovative water treatment technologies, and regulatory measures. However, significant gaps remain, particularly in interdisciplinary approaches and research on developing countries, such as Indonesia. This study recommends advancing scalable, cost-effective hybrid technologies, fostering interdisciplinary collaboration, and promoting public awareness initiatives. This study highlights the need to integrate technological, social, and policy dimensions to address industrial water pollution effectively, offering a pathway for sustainable solutions and future research directions.